O-GlcNAc Modification and the Tauopathies: Insights from Chemical Biology - Yuzwa, Scott A.; Vocadlo, David J. (Current Alzheimer Research, 2009)
The aggregation of the microtubule-associated protein tau into paired-helical filaments is the defining characteristic of the tauopathies. It has become apparent that the hyperphosphorylation of tau likely plays a role in the aggregation process and thus strategies to reduce tau phosphorylation are generating wide interest. The O-GlcNAc posttranslational modification of tau has been shown to be reciprocal to its phosphorylation; increasing O-GlcNAc leads to reductions in tau phosphorylation. In this mini-review, we highlight the use of chemical compounds as a means of understanding the reciprocal nature of tau phosphorylation and tau O-GlcNAcylation and highlight some recent progress in this area.
Keywords: O-GlcNAc